PERAN GURU DALAM MENINGKATKAN MOTIVASI DAN KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN SENI BUDAYA PADA TINGKAT SMP - Naqiyyatu Lestari; Galuh Fatma Hedianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of teachers in enhancing students’ learning motivation and classroom engagement in dance education at SMP Negeri 5 Semarang. The study was motivated by the low level of student participation in dance learning, particularly among male students who are influenced by gender stereotypes. The objective of this research was to analyze how teachers perform their roles as motivators, facilitators, and mentors to improve students’ motivation and active participation in dance learning. This study employed a descriptive qualitative approach. Data were collected through classroom observations, semi-structured interviews, and documentation involving one dance teacher and two eighth-grade students selected through purposive sampling. The validity of the data was ensured through source and technique triangulation, while data were analyzed using data reduction, data display, and conclusion drawing. The findings reveal that teachers play three complementary roles in promoting students’ motivation and engagement. As motivators, teachers increase students’ interest by explaining the educational, cultural, and career benefits of dance. As facilitators, teachers reduce gender stereotypes by selecting appropriate learning materials and presenting successful male role models. As mentors, teachers provide continuous guidance, encouragement, and opportunities for students to perform, resulting in greater confidence and active participation. The study concludes that teachers’ personal and supportive approaches are the primary factors in improving students’ motivation and engagement in junior high school dance learning, highlighting the importance of strengthening teachers’ pedagogical and interpersonal competencies alongside instructional innovation.